Light, Sound, and Waves Science Fair Projects : Using Sunglasses, Guitars, CDs, and Other Stuff - Gardner, Robert (USA Enslow Publishers, 2004)
Simple experiments allow the student to discover why dogs hear things humans don't, why flames give off light, and why some mirrors distort the reflection.
Include Illustrations and Index
Keywords: Sound--Experiments -- Light--Experiments